Adverse Events of the BCG (Bacillus Calmette–Guérin) and Rotavirus Vaccines in a Young Infant with Inborn Error of Immunity - Suleiman Al-Hammadi; Najla S. Alkuwaiti; Ghassan A. Ghatasheh; Huda Al Dhanhani; Hiba M. Shendi; Abdulghani S. Elomami; Farida Almarzooqi; Abdul-Kader Souid (Case Reports in Immunology)
Background. The Bacillus Calmette–Guérin (BCG) and rotavirus vaccines are live-attenuated preparations. In the United Arab Emirates, these products are universally administered to the young infants. This unguided practice does not account for the children with immunodeficiency, which frequently manifests after the administration of these vaccines. We present here a young infant with immunodeficiency that developed disseminated tuberculosis infection and severe diarrhea due to these improper immunizations. Case Presentation. This young infant was diagnosed at six months of age with “immunodeficiency type 19” (MIM#615617) due to homozygous nonsense variant, NM_000732.4 (CD3D):c.128G > A, p.Trp43∗ (variation ClinVar#VCV000643120.1; pathogenic). This variant creates premature stop-gain in CD3D (CD3 antigen, delta subunit, autosomal recessive; MIM#186790), resulting in loss-of-function. He also had “X-linked agammaglobulinemia” (MIM#300755) due to hemizygous missense variant, NM_001287344.1 (BTK):c.80G > A, p.Gly27Asp (novel). He had a sibling who passed away in infancy of unknown disease and family members with autoimmune disorders. Despite these clear clues, he was immunized with BCG at birth and rotavirus at 2 and 4 months. He was well in the first four months. He then developed high-fever, lymphadenopathy, and refractory diarrhea. Stool was positive for rotavirus, and lymph node biopsy showed acid-fast bacilli, consistent with tuberculosis lymphadenitis. These infections were serious and markedly complicated his clinical course, which included bone marrow transplantation from a matched sibling. Conclusions. These unfortunate events could have been avoided by compiling the available clinical information. This patient underscores the importance of implementing proper policies for BCG and rotavirus vaccinations. International registries of adverse events of universally administered vaccines are crucial.